Sustainability policies and practices in public sector organisations: The case of the Portuguese Central Public Administration. (20th November 2018) - Figueira, Inês; Domingues, Ana Rita; Caeiro, Sandra; Painho, Marco; Antunes, Paula; Santos, Rui; Videira, Nuno; Walker, Richard M.; Huisingh, Donald; Ramos, Tomás B.
Abstract: The adoption of sustainability policies and practices in organisations is a rising trend, in particular in companies. Public sector organisations are also following this occurrence but with slower signs. Despite a relevant amount of research work on sustainability practices implemented by private organisations and by some public agencies, central public sectors have been left out of the scope of these studies. The main goal of this research is to identify the sustainability profile (including adopted policies and practices) of the public organisations, using the Portuguese Central Public Administration as a case study. A questionnaire survey was developed and submitted to Portuguese public sector organisations that fulfilled the following criteria: (i) to belong to the Portuguese Central Public Administration and (ii) to have the major area of activity at the national level. The statistical population was also defined on the basis of these criteria. Descriptive statistics and frequency analysis were used to explore the results in the organisations surveyed. The overall results demonstrate a low adoption level of integrated sustainability policies and practices, despite the expected positive trends related with the mandatory social and economic practices. This research contributes to new knowledge by characterising the sustainability profile of the Portuguese central public sector and where actions are needed, leading to a better transition to sustainable societies. The developed questionnaire can be used in other geographical, institutional and cultural contexts to define sustainability profile of worldwide public organisations, working also as a benchmarking tool. Highlights: The adoption of sustainability policies and practices in the Public Sector is mainly unknown. A survey was conducted to identify sustainability policies and practices in the Portuguese central Public Sector. A profile of the sustainability policies and practices in Portuguese central Public Sector was drawn.